Preliminary results from Brazil's first recovery housing program - do Carmo,Dhione Almeida (2018)
Abstract Introduction: The recovery housing (RH) program was initiated in São Paulo with the objective of providing treatment for substance use disorders and addressing users’ housing and employment problems. The purpose of this study was to describe the model based on its first 11 months of operation, it was launched in June 2016 in Brazil. Method: We carried out a retrospective analysis of the records of all subjects treated in the RH of the Restart Program (Programa Recomeço) since its creation, from June 2016 to May 2017. Results: Sixty-nine subjects were included. Thirty-five (51%) remained in the household until the end of treatment or were reinserted in society. Thirty-four (49%) presented recurrence during their stay, of which 16 (47%) volunteered for treatment in a therapeutic community or psychiatric hospital, 8 (23.5%) chose to continue with outpatient treatment only, 6 (17.7%) returned to their families and continued to receive outpatient treatment, and 4 (11.8%) discontinued the treatment. Of the 35 subjects who completed the RH program, 28 (80%) were in employment and 7 (20%) received governmental support for permanent disability on medical or psychiatric grounds. Conclusion: RH can be an important component of integrated care and is used in several countries. Although controversial, the use of urine tests to control relapse seems to have a positive impact on adherence to treatment and maintenance of abstinence. These preliminary findings corroborate, with clear limitations, the evidence available in the literature showing that RH programs are effective for the treatment of addictions.